Religious practice and cultural construction of animal worship in Egypt from the Early Dynastic to the New Kingdom : ritual forms, material display, historical development - Colonna, Angelo (Archaeopress Egyptology, 2021)
This study presents an articulated historical interpretation of Egyptian 'animal worship' from the Early Dynastic to the New Kingdom, and offers a new understanding of its chronological development through a fresh review of pertinent archaeological and textual data.